2016
DOI: 10.1016/j.lungcan.2016.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Metformin use and survival from lung cancer: A population-based cohort study

Abstract: word count: 222 Manuscript word count: 1,472Number of tables and figures: 2 Abbreviations: BMI, body mass index; CIs, confidence intervals; CPRD, Clinical Practice Research Datalink; DDD, daily defined dose; GP, general practitioner; HR, hazard ratio; NCDR, National cancer Data Repository; ONS, Office of National Statistics; UK, United Kingdom; WHO, World Health Organisation. AbstractPreclinical evidence suggests that metformin, a widely prescribed anti-diabetic drug, may inhibit lung cancer progression. We in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 21 publications
0
30
1
Order By: Relevance
“…Notably, neither metformin nor 2DG has exhibited significant adverse side effects in the clinic (Lalau and Race, ; Dwarakanath et al ., ; Stein et al ., ). Metformin and 2DG have been studied in Phase I and II clinical studies in cancer patients (Cheong et al ., ; DePeralta et al ., ; Menamin et al ., ). Previous studies have shown that polycystic kidney cells are similar to tumour cells.…”
Section: Discussionmentioning
confidence: 97%
“…Notably, neither metformin nor 2DG has exhibited significant adverse side effects in the clinic (Lalau and Race, ; Dwarakanath et al ., ; Stein et al ., ). Metformin and 2DG have been studied in Phase I and II clinical studies in cancer patients (Cheong et al ., ; DePeralta et al ., ; Menamin et al ., ). Previous studies have shown that polycystic kidney cells are similar to tumour cells.…”
Section: Discussionmentioning
confidence: 97%
“…These results were replicated in Menamin et al’s study, which assessed lung cancer patient registry between 1998 and 2009, and they found a weak favorable outcome when metformin was on board before or after diagnosis [63]. Interestingly, in the same study, there was a weak negative impact on other hypoglycemic agents like sulphonylureas and thiazolidinedione [63]. Further prospective studies are needed since the data in this perspective are contradicting.…”
Section: Metformin and Cancersmentioning
confidence: 84%
“…However, another meta-analysis including 17 studies showed metformin had no survival benefit when used as an adjuvant with chemo-radiotherapy while it conferred a better survival outcome to lung cancer patients including those on chemotherapy only [62]. These results were replicated in Menamin et al’s study, which assessed lung cancer patient registry between 1998 and 2009, and they found a weak favorable outcome when metformin was on board before or after diagnosis [63]. Interestingly, in the same study, there was a weak negative impact on other hypoglycemic agents like sulphonylureas and thiazolidinedione [63].…”
Section: Metformin and Cancersmentioning
confidence: 99%
“…There have been a few studies examining metformin use and survival among lung cancer patients 2531 . However, the results have been inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…However, in another study of lung cancer patients (NSCLC and small cell lung cancer were not differentiated), pre-diagnostic use of metformin increased risk of death after adjustment for age and tumor stage 26 . Among studies that evaluated post-diagnostic metformin use 2527, 29, 31 , a recent retrospective cohort study reported a non-significant HR of 0.86 (95% CI, 0.68 to 1.09) for lung cancer-specific mortality 31 , after adjustment for multiple variables, although cancer stage was not adjusted and NSCLC and small cell lung cancer were not differentiated. A small clinical trial reported improved overall survival with metformin use compared to those on other anti-diabetic drugs among advanced stage NSCLC patients 27 , while another small study found similar overall survival between patients with and without metformin use among locally advanced NSCLC patients 29 .…”
Section: Discussionmentioning
confidence: 99%